An interplay between the p38 MAPK pathway and AUBPs regulates c-fos mRNA stability during mitogenic stimulation - Degese, María Sol (2015)
Mitogen-activated protein kinase (MAPK) pathways constitute key regulatory elements linking extracellular stimuli to nuclear gene expression. Immediate-early responsive genes (IEGs) of the activator protein 1 (AP-1) family, such as fos, achieve peak expression levels shortly after cells are stimulated with growth factors and sharply decrease thereafter. Several AU-rich binding proteins (AUBPs), including HuR (Hu-antigen R, Elavlike protein 1, ELAVL1) and KSRP (far upstream element-binding protein 2, KHSRP) bind to a fos AU-rich element (ARE) present in the 3′-UTR (untranslated region) of fos mRNA regulating its stability by a still poorly defined mechanism. We show in the present study that, whereas HuR binds and stabilizes transcribed reporter mRNAs bearing the fos 3′-UTR, KSRP counteracts this effect. Furthermore, we found that fos mRNA stability and HuR phosphorylation status are dependent on the activity of p38 MAPK in both epithelial cells and fibroblasts upon proliferative stimulation. Analysing PPI (protein-protein interaction) networks, we performed a thorough query of interacting proteins for p38 MAPKs, HuR and other AUBPs upon growth factor stimulation. This revealed novel HuR interactors including inhibitors of protein phosphatase 2 (PP2A) activity. Over-expression of two of these interactors, pp32 and APRIL (acidic leucine-rich nuclear phosphoprotein 32 family member B, ANP32B) and pharmacological inhibition of PP2A stabilized a fos reporter mRNA. Our results indicate that p38 MAPK regulates fos mRNA decay by affecting the state of phosphorylation of HuR while controlling yet to be fully elucidated PP regulatory networks.